Psi-Caller: A Lightweight Short Read-Based Variant Caller With High Speed and Accuracy - Liu, Yadong; Jiang, Tao; Gao, Yan; Liu, Bo; Zang, Tianyi; Wang, Yadong (Frontiers in Cell and Developmental Biology, 2021)
With the rapid development of short read sequencing technologies, many population-scale resequencing studies have been carried out to study the associations between human genome variants and various phenotypes in recent years. Variant calling is one of the core bioinformatics tasks in such studies to comprehensively discover genomic variants in sequenced samples. Many efforts have been made to develop short read-based variant calling approaches, however, state-of-the-art tools are still computationally expensive, meanwhile, cutting-edge genomics studies also have higher requirements on the yields of variant calling. Herein, we propose Partial Order Alignment-based SNV and Indel caller (Psi-caller), a lightweight variant calling algorithm that simultaneously achieves high performance and yield. Mainly, Psi-caller recognizes and divides the candidate variant site into three categories according to the complexity and location of the signatures, and employs various methods including binomial model, partial-order alignment and de-Bruijn graph-based local assembly to handle various categories of candidate variant sites to call and genotype SNVs/Indels, respectively. Benchmarks on simulated and real short-read sequencing datasets demonstrate that Psi-caller is times faster than state-of-the-art tools with higher or equal sensitivity and accuracy. It has the potential to well-handle large-scale datasets in cutting-edge genomics studies.